Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/md.0000000000022363
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain level in traumatic brain injury

Abstract: Background: Neurofilament light (NfL) level was obviously increased in traumatic brain injury (TBI) individuals. But, no comprehensive meta-analysis has ever been conducted to assess the diagnostic performance of NfL. This study aims to evaluate the relationship between NfL level and TBI through a meta-analysis. Methods: Studies were selected from Pubmed, Web of science, Embase, Google Scholar, PMC and Chinese National Knowledge Infrastructure (CNKI), and the Chinese Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…Similar to tau protein, NfL functions as a scaffolding structural protein in axonal and dendritic branching and growth, and NfL undergoes post-translational modification by a series of phosphorylation events, which can make it vulnerable to mechanical stretch and shear stress ( 62 ). Growing evidence supports that NfL levels in blood have shown to reflect the progression of neurodegenerative condition (e.g., Alzheimer's disease, multiple sclerosis) ( 63 65 ), differentiate severities of TBI ( 66 ), predict clinical outcome (e.g., functional recovery, return-to-play) after severe TBI and concussion ( 67 , 68 ), and correlate with subconcussive head impact exposure ( 24 , 26 , 32 , 33 ). Unlike tau, however, we failed to observe significant correlations between NfL and diffusion metrics, which opposes the data by Ljungqvist et al ( 69 ) that showed an association between serum NfL and FA ( R 2 = 0.83) 12 months after severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to tau protein, NfL functions as a scaffolding structural protein in axonal and dendritic branching and growth, and NfL undergoes post-translational modification by a series of phosphorylation events, which can make it vulnerable to mechanical stretch and shear stress ( 62 ). Growing evidence supports that NfL levels in blood have shown to reflect the progression of neurodegenerative condition (e.g., Alzheimer's disease, multiple sclerosis) ( 63 65 ), differentiate severities of TBI ( 66 ), predict clinical outcome (e.g., functional recovery, return-to-play) after severe TBI and concussion ( 67 , 68 ), and correlate with subconcussive head impact exposure ( 24 , 26 , 32 , 33 ). Unlike tau, however, we failed to observe significant correlations between NfL and diffusion metrics, which opposes the data by Ljungqvist et al ( 69 ) that showed an association between serum NfL and FA ( R 2 = 0.83) 12 months after severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the detection of neurofilaments in blood is used both in humans and animals as a way to monitor neuronal damage. 65 , 66 , 67 , 68 , 69 In this context, it is important that general anesthesia alters blood neurofilament concentrations already in neurologically healthy individuals. 70 , 71 Moreover, given that isoflurane anesthesia in rodents slows down brain drainage via the cerebrospinal fluid, 72 , 73 this may result in an underestimation of neurofilament disruption occurring in the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we evaluated phosphorylated tau-181 (ptau181), and amyloid beta (Aβ)-40 and 42, which are more specific biomarkers for Alzheimer's type pathology (10,(13)(14)(15). Notably, UCH-L1 (16,17), GFAP (18), tau (18), and NFL (19,20) are also elevated following blood brain barrier disruption, which has been documented in neuropathological studies of COVID-19 decedents(21) as well as in AD.…”
Section: Introductionmentioning
confidence: 99%